Pengembangan Media Pembelajaran Interaktif Quizizz pada Pembelajaran Bahasa Arab untuk Meningkatkan Kemampuan Mufrodat dan Qowaid di MTsN 3 Kediri - Muthongah, Binti Mar’atul; Saidah, Ratna; Hartanto, Eko Budi (Al-Wasil, 2024)
Media plays an important role in the learning process, therefore different types of media appear and many updates along with the development of technology. Choosing the right media can increase student interest and have a positive impact on their success. But in fact, the use of technology-based media has not been widely applied in some schools. One of them is MTsN 3 Kediri included in class VIII. The purpose of this study is to describe Quizizz Learning Media in Arabic Learning for Class VIII MTSN 3 Kediri Students. This type of research is Research and Development (R&D) using the ADDIE model: analysis, design, develop, implement, and evaluate. This study was conducted from January to February in class VIII-B which amounted to 36 students. The design used is a trial of one group pretest-postest design. In the results of research on the development of Quizizz learning media in Arabic language learning grade VIII B MTsN 3 Kediri with a feasibility level through validation tests to media experts, material experts and learning experts. an average score of 89% was obtained which was included in the "very decent" category. Meanwhile, based on the results of the analysis of media attractiveness according to students obtained a score of 88%. Which score is included in the "Very Interesting" category. While the level of media effectiveness is obtained from students' pre-test and post-test results, with the average pre-test score is 60 while the average post-test score is 87. At the t-test stage with a signification level of 0.05, the result of Tcalculate 13.26 was obtained while Ttable 1.67 which means Ho was rejected and Ha was accepted, so it can be concluded that there is a significant difference in the average score of students before and after applying the product from the development results. With the development of Arabic language learning media through Quizizz, Arabic language knowledge is also developing following the millennial era.